Mental and Emotional Disorders of Patients with Oncological Diseases (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Oncological diseases increase the mental and emotional state of patients. Fighting with such diseases creates a unique problem and many consequences. Patients may experience emotional and psychological changes related to themselves, their life indicators, and the way they live their changed lives. It is also important for cancer patients to receive the treatments and medical care they receive. It is very important to maintain relationships with patients and to support them well, understand their problem, and provide emotional and spiritual support regarding their life directions.